2014
DOI: 10.4103/1463-1741.127847
|View full text |Cite
|
Sign up to set email alerts
|

Updated exposure-response relationship between road traffic noise and coronary heart diseases: A meta-analysis

Abstract: A meta-analysis of 14 studies (17 individual effect estimates) on the association between road traffic noise and coronary heart diseases was carried out. A significant pooled estimate of the relative risk of 1.08 (95% confidence interval: 1.04, 1.13) per increase of the weighted day-night noise level L DN of 10 dB (A) was found within the range of approximately 52-77 dB (A) (5 dB-category midpoints). The results gave no statistically significant indication of heterogeneity between the results of individual stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
136
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(153 citation statements)
references
References 22 publications
5
136
0
4
Order By: Relevance
“…Pri hladinách A hluku nad 60 dB riziko vzniku infarktu myokardu kontinuálne narastá s rizikom od 1,1-1,5 (50). Posledná metaanalýza poukázala na 8% nárast rizika (relatívne riziko 1,08 (95 % IS = 1,04-1,13) pri každom náraste váženej hladiny A hluku počas dňa a noci L dn o 10 dB v expozičnej kategórií 52-77 dB (51,52). Argalášová-Sobotová a kol.…”
Section: Hluk a Kardiovaskulárny Systémunclassified
“…Pri hladinách A hluku nad 60 dB riziko vzniku infarktu myokardu kontinuálne narastá s rizikom od 1,1-1,5 (50). Posledná metaanalýza poukázala na 8% nárast rizika (relatívne riziko 1,08 (95 % IS = 1,04-1,13) pri každom náraste váženej hladiny A hluku počas dňa a noci L dn o 10 dB v expozičnej kategórií 52-77 dB (51,52). Argalášová-Sobotová a kol.…”
Section: Hluk a Kardiovaskulárny Systémunclassified
“…However, the impacts of the remaining factors are lower compared with traffic noise, in terms of noise levels and amount of annoyance for individuals. On the basis of the conducted studies, noise pollution can have various effects on health, including hypertension, risk of heart disease, impact on sleep, psychological effects, annoyance and disruption of daily activities, fatigue, decreased performance in school children, interference with daily life and other effects (1)(2)(3)(4)(5)(6)(7). The impacts of noise pollution on peoples' sleep and health have been confirmed by various laboratory, field, epidemiology and review studies (8)(9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 96%
“…Data show that exposure to traffic noise, not specifically at night, is associated with increased incidence of diabetes [17], hypertension [24], as well as increased incidence and mortality from coronary heart disease [25], [26]. In their study, Orban et al, [27], concluded that long-term exposure to road traffic noise may increase the risk of depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%